1995
DOI: 10.1136/jmg.32.4.269
|View full text |Cite
|
Sign up to set email alerts
|

Association study with two markers of a human homeogene in infantile autism.

Abstract: Epidemiological data and family studies in autism show that there is a genetic susceptibility factor in the aetiology of this syndrome. We carried out an association study in infantile autism. Two markers of the homeogene EN2 involved in cerebellar development were tested in a population of 100 autistic children and in a population of 100 control children. With the MP4 probe showing a PvuII polymorphism, significant differences in the allele frequencies between the two populations were found (x2=7-99, df=1, p<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
2
4

Year Published

1997
1997
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(60 citation statements)
references
References 41 publications
2
52
2
4
Order By: Relevance
“…Seen in this light, Engrailed seems to capture many aspects of the autistic brain and has the potential to unveil many more. To date, three genetic studies have linked the human En2 gene to autism [13,32,51]. These studies concur with reports that describe the broad similarities between the neuropathology of the En2 −/− mouse and a subset of features commonly found in autism.…”
Section: Introductionsupporting
confidence: 70%
“…Seen in this light, Engrailed seems to capture many aspects of the autistic brain and has the potential to unveil many more. To date, three genetic studies have linked the human En2 gene to autism [13,32,51]. These studies concur with reports that describe the broad similarities between the neuropathology of the En2 −/− mouse and a subset of features commonly found in autism.…”
Section: Introductionsupporting
confidence: 70%
“…Currently, few studies on candidate genes which converge on linkage signals have been consistently associated with autism (Folstein and Rosen-Sheidley, 2001;Bartlett et al, 2005). Among them, and within a widely confirmed linkage region in the long arm of chromosome 7, recent evidence has shown that Wnt2 and Engrailed 2 (EN2), a Wnt/b-catenin target gene (McGrew et al, 1999), may be genetically associated with autism (Petit et al, 1995;Wassink et al, 2001;McCoy et al, 2002;Zhong et al, 2003;Gharani et al, 2004;Benayed et al, 2005).…”
Section: Wnt Signaling and Autismmentioning
confidence: 99%
“…At present, several polymorphisms in exons as well as introns and regulatory regions of the EN2 gene have been genotyped in different autistic samples including families coming from the Autism Genetic Resource Exchange (AGRE) initiative as well as to the NIMH Center for Collaborative Genetic Studies (Petit et al, 1995;Zhong et al, 2003;Gharani et al, 2004;Benayed et al, 2005). Previous studies found an association of a PvuII restriction fragment length polymorphism located in the 5 0 UTR region of EN2 in 100 autistic children and 100 control children (Petit et al, 1995). More recently, in a large number of nuclear families it was demonstrated that two intronic SNPs (SNP id: rs1861972 and rs1861973) were highly associated with the autistic phenotype, both in single locus tests as well as in haplotype analysis (Gharani et al, 2004;Benayed et al, 2005).…”
Section: Wnt Signaling and Autismmentioning
confidence: 99%
“…[191][192][193][194] EN2 is a homeobox transcription factor that plays a role during cerebellar and brainstem development.…”
mentioning
confidence: 99%